Sistem Informasi E-Logistik Pada Siklus Proses Order BahanBaku - Diana Karlina W.P.; Soetam Rizky Wicaksono (Universitas Atma Jaya Yogyakarta, 2014)
Abstract. Logistics activities have a big role in a company because it is the core of the company’s activities. The utilization of e-logistics is essential as it will make the company more efficient. PT. XYZ is one of glass tube manufacturer with the production reaching up to 90,000 units of each day that causes the manufacturer takes a lot of components or raw materials, in which the raw materials required by the company are obtained from many suppliers. The process of procurement of supplies is carried out by the purchase order process. Information in the form of purchase order is submitted to the supplier, where the supplier is a partner of the companies involved in the flow of the materials. Logistic does not stop at booking, but includes the logistics flow of demand information of raw materials, as well as the process and stock storage of finished product and raw materials, and to the point where finished goods are shipped to the consumers. With the application of e-logistics, companies are expected to be able to collect and process the flow of information in the process of getting the raw materials and products in the production process, to create and maintain the cooperation between enterprises and suppliers in inventory control so that the process can be carried out efficiently.Keywords: logistic, supply chain management, e-logisticAbstrak. Kegiatan logistik berperan besar di dalam sebuah perusahaan karena merupakan pusat operasional dari perusahaan. Pemanfaatan e-logistik sangat berguna, karena akan membuat perusahaan semakin efisien. Demikian pula halnya pada PT. XYZ salah satu perusahaan glasstube dengan produksi mencapai 90.000 satuan setiap harinya di mana pembuatan glasstube membutuhkan banyak komponen/ bahan baku, di mana bahan baku yang dibutuhkan oleh perusahaan didapatkan dari banyak supplier dan perusahaan pemasok lain. Informasi berupa order pembelian akan disampaikan kepada supplier, di mana supplier merupakan mitra perusahaan yang terlibat dalam aliran material. Tidak hanya berhenti pada proses pemesanan, namun logistik juga meliputi aliran informasi permintaan bahan baku, serta proses penyimpanan stok produk jadi maupun bahan baku, hingga barang jadi dikirimkan kepada konsumen. Dengan penerapan e-logistik diharapkan perusahaan mampu memproses aliran informasi dalam proses pemenuhan bahan baku dan produk dalam proses produksinya, membentuk kerjasama antara perusahaan dan supplier dalam pengendalian persediaan sehingga proses tersebut dapat dilakukan secara efisien.Kata Kunci:logistik, supply chain management, e-logistik